Business ethics at the crossroads - Cooke, Robert Allan (Journal of business ethics, 1986)
During the last decade, the intensity of interest in the subject of business ethics has surprised even the most ardent defenders of the movement. It is easy to become euphoric over such developments. Yet, we should not be lulled into believing that such growth has no limits. The fact is that the movement stands at a watershed where certain alternative courses of action are available. In this paper, I outline what some of those crossroads are and what the consequences will be if certain actions are or are not taken. The key to success is dependent upon a multidisciplinary approach that relies on dialogue and cooperation among colleagues in the academy and in business. This will ensure a true mix of theory and practice.